Analisis Tingkat Partisipasi Masyarakat Dalam Aktivitas Olahraga Saat Car Free Day Di Kabupaten Gresik - Dheo Andika Ali; Abdul Aziz Hakim; Made Pramono; Testa Adi Nugraha (Lembaga Pengembangan Kinerja Dosen, 2024)
The phenomenon of rapidly developing life is occurring swiftly in human life. This rapid development certainly poses challenges for human life. Car Free Day is one of the activities designed by the government to address these challenges. The success of this program can be seen from the level of public participation. Therefore, this study aims to analyze the level of community participation in sports activities during Car Free Day in Gresik Regency. Additionally, this study identifies that public participation in Car Free Day is also influenced by several factors, such as the sports activities available during Car Free Day, the number of interesting attractions at Car Free Day, the location of the Car Free Day event, the weather, the facilities provided, and the safety during the event. The method used in this research is a survey method with a descriptive quantitative approach. Data collection was carried out through questionnaires distributed to Car Free Day participants and direct observation at the event location. The research results show that the level of public participation in sports activities during Car Free Day in Gresik Regency is relatively high, with 46.7% rarely participating in Car Free Day activities. Most respondents who participate in Car Free Day activities are primarily motivated by the desire to exercise. The most common exercise among respondents is walking. The majority of respondents are male. Furthermore, most respondents are in the 15-25 age group, which is the student age group. Based on this, the researchers recommend increasing public participation in Car Free Day in Gresik Regency. These recommendations include adding and improving the quality of sports facilities, adding more diverse and interesting programs, and promoting the benefits of exercise. Thus, it is hoped that Car Free Day can become a means to encourage the community to adopt a healthy lifestyle through exercise.